2010
DOI: 10.1091/mbc.e09-05-0440
|View full text |Cite
|
Sign up to set email alerts
|

Live-Cell Imaging in Caenorhabditis elegans Reveals the Distinct Roles of Dynamin Self-Assembly and Guanosine Triphosphate Hydrolysis in the Removal of Apoptotic Cells

Abstract: During cell corpse removal, dynamin's self-assembly and GTP hydrolysis activities establish a precise dynamic control of DYN-1's transient association to its target membranes. Dynamin's dynamic membrane association controls the mechanism that underlies the recruitment of downstream effectors, such as small GTPases RAB-5 and RAB-7, to target membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 62 publications
2
47
0
Order By: Relevance
“…Surprisingly, the assembly of MxA onto liposomes did not change GTP hydrolysis whereas liposome binding of dynamin increased nucleotide hydrolysis about 20-fold, as expected (Fig. 4) (26,28,42). Intracellular membranes are the active sites of dynamin action.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Surprisingly, the assembly of MxA onto liposomes did not change GTP hydrolysis whereas liposome binding of dynamin increased nucleotide hydrolysis about 20-fold, as expected (Fig. 4) (26,28,42). Intracellular membranes are the active sites of dynamin action.…”
Section: Discussionsupporting
confidence: 79%
“…Both MxA and dynamin form tetramers in solution with a low basal rate of nucleotide hydrolysis (8,18) and are known to form higher order oligomers at elevated protein concentrations as well as on lipid membranes (16, 19 -22). Self-assembly leads to increased GTP hydrolysis rates (8,18,23,24), and interaction of dynamin with lipid bilayers via its PH domain further enhances assembly-stimulated GTP hydrolysis (25)(26)(27)(28). To investigate the function of lipid interaction for MxA and identify the region responsible for membrane binding, we performed a detailed study of the membrane binding properties of MxA using biochemical assays as well as cryo-transmission electron microscopy (cryo-TEM).…”
mentioning
confidence: 99%
“…Membrane-bound, GTP-bound Rab proteins act as tethering factors to promote organelle-organelle or organellemembrane fusion. RAB-5 is detected on the phagosomal membrane once the nascent phagosome is formed during cell corpse clearance (He et al 2010). The recruitment of RAB-5 and its effector VPS-34 to phagosomes is mutually dependent and DYN-1-dependent, suggesting a model in which DYN-1 acts upstream of RAB-5 and VPS-34, while RAB-5 and VPS-34 may act as a positive feedback system ( Figure 4A) (Kinchen et al 2008;He et al 2009).…”
Section: Formation and Maturation Of Phagosomesmentioning
confidence: 99%
“…2b). Detailed studies on dyn-1 revealed its function in both steps of apoptotic cell removal [121,122]. During the engulfment phase, DYN-1 ensures the rapid expansion of phagocyte membrane along the surface of dying cells by organizing vesicle transport and promoting fusion of early endosomes to extending pseudopods [121,122] (Fig.…”
Section: Ndpks As Signal Integrators Of Nutrient Supplymentioning
confidence: 99%
“…2b). Recruitment of two endosomal markers, RAB-5 and RAB-7, also relies on DYN-1 activity [122][123][124]. RAB-5 is important for promoting the maturation of phagosomes containing apoptotic cells [124,125].…”
Section: Ndpks As Signal Integrators Of Nutrient Supplymentioning
confidence: 99%